Sensitivity of summer ensembles of fledgling superparameterized U.S. mesoscale convective systems to cloud resolving model microphysics and grid configuration. (1st May 2016) - Elliott, Elizabeth J.; Yu, Sungduk; Kooperman, Gabriel J.; Morrison, Hugh; Wang, Minghuai; Pritchard, Michael S.
Abstract: The sensitivities of simulated mesoscale convective systems (MCSs) in the central U.S. to microphysics and grid configuration are evaluated here in a global climate model (GCM) that also permits global‐scale feedbacks and variability. Since conventional GCMs do not simulate MCSs, studying their sensitivities in a global framework useful for climate change simulations has not previously been possible. To date, MCS sensitivity experiments have relied on controlled cloud resolving model (CRM) studies with limited domains, which avoid internal variability and neglect feedbacks between local convection and larger‐scale dynamics. However, recent work with superparameterized (SP) GCMs has shown that eastward propagating MCS‐like events are captured when embedded CRMs replace convective parameterizations. This study uses a SP version of the Community Atmosphere Model version 5 (SP‐CAM5) to evaluate MCS sensitivities, applying an objective empirical orthogonal function algorithm to identify MCS‐like events, and harmonizing composite storms to account for seasonal and spatial heterogeneity. A five‐summer control simulation is used to assess the magnitude of internal and interannual variability relative to 10 sensitivity experiments with varied CRM parameters, including ice fall speed, one‐moment and two‐moment microphysics, and grid spacing. MCS sensitivities were found to be subtle with respect to internal variability, and indicate that ensembles of over 100 storms may be necessary to detect robust differences in SP‐GCMs. These results emphasize that the properties of MCSs can vary widely across individual events, and improving their representation in global simulations with significant internal variability may require comparison to long (multidecadal) time series of observed events rather than single season field campaigns. Key Points: Internal variability of U.S. MCS events dominate CRM sensitivities in superparameterized CAM Need ensembles of 100+ storms to detect sensitivities and tune superparameterized physics